Knowledge, Attitudes, and Practices Regarding Antibiotic Use for Children Among Mothers Living in Islamabad - Muhammad Huzaifa Mazhar, Muhammad Bilal Zafar, Muhammad Umair Javed, Zoha Khalid, Zille Huma Mustehsan, Iffat Noreen, Areeba Nawaz, Musfira Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The escalating incidence of antibiotic resistance is a critical global health threat, disproportionately affecting developing nations like Pakistan due to the excessive and unnecessary use of antibiotics in children. Aim & Objectives: This study aims to assess the knowledge, attitudes, and practices regarding antibiotic use among mothers for their children under 10 years of age living in Islamabad. Methodology: An analytical cross-sectional study was conducted using purposive sampling, involving 246 mothers from various hospital outpatient departments and malls in Islamabad. Data were collected via a self-administered questionnaire and analyzed using SPSS version 23.0 to determine associations using chi-square tests. Results: Among the 246 participants, 48.37% had poor, 46.34% had moderate, and only 5.28% demonstrated good knowledge of antibiotics. Regarding attitudes, 63.41% exhibited a satisfactory approach, while 51.22% showed good practices. A significant positive association was observed between maternal education and antibiotic knowledge (p = 0.050), and between knowledge and practice (p = 0.002). Additionally, 38.6% of mothers reported purchasing antibiotics without a doctor’s prescription. Conclusion: Significant misconceptions regarding the indications and use of antibiotics exist among mothers, alongside a prevalent lack of knowledge about antibiotic resistance. Despite some awareness of the associated risks, inappropriate practices like using unprescribed antibiotics persist. Keywords: Antibiotic Resistance, Knowledge, Attitudes, Practices, Mothers, Pakistan, Self-medication.